The enzymes OSC1 and CYP716A263 produce a high variety of triterpenoids in the latex of Taraxacum koksaghyz - Pütter, Katharina M. (Sci Rep, 2019)
Only very little is known about the resin composition of natural rubber from the dandelion species Taraxacum koksaghyz, thus its full characterization could provide new insights into how the isoprenoid end-products influence the physical properties of natural rubber, and this resin might be a good source of highly diverse triterpenoids. Here, we present a comprehensive analysis of the triterpenoid composition in an acetone extract and identified 13 triterpenes and triterpenoids also including the so far unknown pentacyclic compounds lup-19(21)-en-3-ol (1) and its ketone lup-19(21)-en-3-one (2). We purified single triterpenes from the acetone extract by developing a two-step HPLC system that is adapted to the structural differences of the described triterpenoids. Furthermore, we isolated six different oxidosqualene cyclases (OSCs) and two P450 enzymes, and we functionally characterized TkOSC1 and CYP716A263 in Nicotiana benthamiana and Saccharomyces cerevisiae in detail. TkOSC1 is a multifunctional OSC that was capable of synthesizing at least four of the latex-predominant pentacyclic triterpenes (taraxasterol, α-, β-amyrin and lup-19(21)-en-3-ol) while CYP716A263 oxidized pentacyclic triterpenes at the C-3 position. The identified enzymes responsible for biosynthesis and modification of pentacyclic triterpenes in T. koksaghyz latex may represent excellent tools for bioengineering approaches to produce pentacyclic triterpenes heterologously.